2018
DOI: 10.1177/2399808318784597
|View full text |Cite
|
Sign up to set email alerts
|

Making the case for simulation: Unlocking carbon reduction through simulation of individual ‘middle actor’ behaviour

Abstract: This paper makes the case for agent-based modelling as a route to unlocking the potential of existing buildings to reduce energy demand and contribute to achieving carbon reduction targets. The construction of a model to simulate this system requires significant innovation in data collection and handling. The need to focus on ‘middle actors’ in construction – specifically the tradesmen who carry out repair, maintenance and renovation – in order to reduce energy demand in existing buildings is described. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The strength of middle actors stems from their perception as reliable and legitimate by other actors in the policy domain, and from their unique qualities which other actors in the system are short of or lack, such as tacit knowledge and skills, unique access to nancial resources and other assets, social and professional legitimacies, and unique communication channels [46,47]. Previous studies which applied to the MOP in the eld of energy and the eld of public health demonstrated how middle actors ll the functions of (1) aggregators of assets and nancial resources, thus supporting and coordinating valuable actions; (2) mediators between policymakers and the public, thus making relevant information and regulation accessible to the public, and at the same time re ecting the public's needs and concerns to policymakers; and (3) enablers of actions by having the knowledge and capability to tackle physical, technical and bureaucratic di culties [46,59,60].…”
Section: The Middle-out Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The strength of middle actors stems from their perception as reliable and legitimate by other actors in the policy domain, and from their unique qualities which other actors in the system are short of or lack, such as tacit knowledge and skills, unique access to nancial resources and other assets, social and professional legitimacies, and unique communication channels [46,47]. Previous studies which applied to the MOP in the eld of energy and the eld of public health demonstrated how middle actors ll the functions of (1) aggregators of assets and nancial resources, thus supporting and coordinating valuable actions; (2) mediators between policymakers and the public, thus making relevant information and regulation accessible to the public, and at the same time re ecting the public's needs and concerns to policymakers; and (3) enablers of actions by having the knowledge and capability to tackle physical, technical and bureaucratic di culties [46,59,60].…”
Section: The Middle-out Perspectivementioning
confidence: 99%
“…businesses [48] and social groups [57,59] performed middle-out strategies and promoted the transition to a low carbon society in various ways. These studies focused mainly on the in uence on top and bottom actors.…”
Section: The Middle-out Perspectivementioning
confidence: 99%